Application of Induced Polarization and Resistivity to the Determination of the Location of Metalliferous Veins in the Taroucht and Tabesbaste Areas (Eastern Anti-Atlas, Morocco) - Ibrahim Dakir; Ahmed Benamara; Habiba Aassoumi; Abdessalam Ouallali; Youssef Ait Bahammou (International Journal of Geophysics)
The study area is located in the extreme southwest of the Ougnat Mountains in the eastern Anti-Atlas, which is part of the distorted northern margin of the West African craton. It has Late Neoproterozoic to terminal, Paleozoic and Quaternary lands. In order to obtain a better recognition of the different structural contacts and to define the alignment of mineralized veins in barite and galena at the level of the study area, we used the technique of electrical tomography. The resulting response, in the form of electrical imaging, informed us in detail about the different zones of heterogeneity existing in the prospected soil. In induced polarization, the pseudosections obtained were able to locate the passages of the zones of anomalies encountered and thus confirm their alignments defined by the electrical resistivity measurement results.